Storage oil hydrolysis during early seedling growth - Quettier, A.L.; Eastmond, P.J.
Storage oil breakdown plays an important role in the life cycle of many plants by providing the carbon skeletons that support seedling growth immediately following germination. This metabolic process is initiated by lipases (EC: 3.1.1.3), which catalyze the hydrolysis of triacylglycerols (TAGs)to release free fatty acids and glycerol. A number of lipases have been purified to near homogeneity from seed tissues and analysed for their in vitro activities. Furthermore, several genes encoding lipases have been cloned and characterised from plants. However, only recently has data been presented to establish the molecular identity of a lipase that has been shown to be required for TAG breakdown in seeds. In this review we briefly outline the processes of TAG synthesis and breakdown. We then discuss some of the biochemical literature on seed lipases and describe the cloning and characterisation of a lipase called SUGARDEPENDENT1, which is required for TAG breakdown in Arabidopsis thaliana seeds.
Keywords: TRIACYLGLYCEROL; LIPASE; SEED; GERMINATION; ARABIDOPSIS